Language Use of The Community of Drugs Abuse in Sinjai District, Sociolinguistic Study - Fatahuddin Burhanuddin; Tadjuddin Maknun; Ery Iswary (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2022)
The use of language among drug abusers community. The distribution and incidents of drug abuse currently become a matter of great concern in our country. In practice, a community of drug offenders who have become convicts uses specific languages in carrying out their actions. Of course, the use of that language has its purpose. Departing from this phenomenon, sociolinguistic research is needed to describe and explain the classification, meaning of language, and the purpose of language use. This study used a language variety theory design in sociolinguistics with a qualitative descriptive method. The results of this study described seven language classifications and meanings of community language, Besides, there is a certain use of secret language from the community of drug abusers, namely as a means of communication in the community and protecting the community from access by other people or other groups. Keywords: Community Language, Drug Abusers, Sinjai